Unique Role of Caffeine Compared to Other Methylxanthines (Theobromine, Theophylline, Pentoxifylline, Propentofylline) in Regulation of AD Relevant Genes in Neuroblastoma SH-SY5Y Wild Type Cells - Janitschke, Daniel (Int J Mol Sci, 2020)
Methylxanthines are a group of substances derived from the purine base xanthine with a methyl group at the nitrogen on position 3 and different residues at the nitrogen on position 1 and 7. They are widely consumed in nutrition and used as pharmaceuticals. Here we investigate the transcriptional regulation of 83 genes linked to Alzheimer’s disease in the presence of five methylxanthines, including the most prominent naturally occurring methylxanthines—caffeine, theophylline and theobromine—and the synthetic methylxanthines pentoxifylline and propentofylline. Methylxanthine-regulated genes were found in pathways involved in processes including oxidative stress, lipid homeostasis, signal transduction, transcriptional regulation, as well as pathways involved in neuronal function. Interestingly, multivariate analysis revealed different or inverse effects on gene regulation for caffeine compared to the other methylxanthines, which was further substantiated by multiple comparison analysis, pointing out a distinct role for caffeine in gene regulation. Our results not only underline the beneficial effects of methylxanthines in the regulation of genes in neuroblastoma wild-type cells linked to neurodegenerative diseases in general, but also demonstrate that individual methylxanthines like caffeine mediate unique or inverse expression patterns. This suggests that the replacement of single methylxanthines by others could result in unexpected effects, which could not be anticipated by the comparison to other substances in this substance class.